Weldability characteristics of friction-welded AISI 2205 to AISI 1020 steels - Mercan, Serdar; Ozdemir, Niyazi (Springer Heidelberg, 2017)
The purpose of this study is to investigate mechanical and microstructure properties of AISI 2205 and AISI 1020 steel couples joined by using friction welding method and having different chemical compositions. Therefore, macroscopic examinations of specimens joined by using different welding parameters were performed and their mechanical properties were determined by using tension and fatigue tests. Effects of welding parameters on joint interfaces were completed by microhardness measurements and SEM analysis. Consequently, it was determined that mechanical and microstructure properties of AISI 2205 and AISI 1020 steel couples changed based on welding parameters and the quality of the joint could be enhanced in case that parameters compatible with each other were selected.
Keywords: Friction welding; Dissimilar materials; Mechanical properties; Microstructure; Fatigue tests